(untitled) (Research, Society and Development, 2022)
Objective: To verify which are the strategies used by high school teachers to face stressful situations in the teaching-learning process. Methodology: This is an integrative literature review. The databases used for literature search were MEDLINE, PsycoINFO, COCHRANE library, CINAHL, and Web of Science. Results: Thirteen studies were selected, eight of which used a cross-sectional design, two were longitudinal and three were intervention studies. The articles were grouped into two categories: evaluation of stress management programs and coping mechanisms used by teachers. The studies showed that, after the application of stress management programs, there was a reduction in the level of stress and an increase in the use of coping strategies. Among these strategies, there were leisure activities, physical activity, walking with pets, socializing with family and friends, the ability to control work tasks, avoid accumulation of activities and understand that these will not always turn out perfect. In addition, dysfunctional coping strategies were cited, in which teachers showed behavioral disengagement, denial, distraction, guilt, substance use, and breathing techniques in order to control stress. Conclusion: Teachers resort to strategies for coping with stressful situations, being them focused on the problem, emotion, relationship, dysfunctional coping and avoidance focus. Stress management programs proved to be efficient in helping teachers to face the challenges imposed by the profession.